The COVID‐19 pandemic and agricultural education: An exploration of challenges faced by teachers. Issue 1 (12th June 2021) - McKim, Aaron J.; Sorensen, Tyson J.; Burrows, Michelle
Abstract: Exploring the challenges faced by agriculture teachers during the Spring 2020 semester brings to light the reality of teaching during the COVID‐19 pandemic. Further, understanding the challenges faced by teachers empowers the profession to make agricultural education more resilient to broader, social forces in the future. In this study, a national sample of agriculture teachers were asked to identify the three most pressing challenges they experienced during the COVID‐19 pandemic. Using qualitative research methods, eight challenge themes emerged: (a) Communication, (b) FFA (National FFA Organization, a student leadership organization previously named the "Future Farmers of America"), (c) Instructional Quality, (d) Program Facilities and Activities, (e) Supervised Agricultural Experiences (SAE), (f) Student Motivation, (g) Technology and the Internet, and (h) Work‐Life Balance. Using quasi‐statistical methods, the most commonly reported challenges were identified ‐ Instructional Quality, FFA, and Student Motivation. Analysis of all the challenges suggested permeation across each aspect of the three‐component model of agricultural education. Furthermore, many challenges appeared to be related to each other. Finally, analysis of the results illuminated responding teachers, and their students, each experienced the challenges brought about by COVID‐19 differently, including evidence of exacerbated educational inequality for students from lower income households. Core Ideas: Hands‐on nature of agricultural education was challenging to transition to remote instruction. Instruction, student organization management, and motivation were the most common challenges. The challenges experienced by teachers during COVID‐19 were interconnected. The challenges experienced during COVID‐19 differed substantially among individuals.